Damage monitoring using fiber optic sensors and by analysing electro-mechanical admittance signatures obtained from piezo sensor - Maheshwari, Muneesh (2018)
Damage monitoring is the need of the hour in this age of infrastructure. Many methods are being used for damage monitoring in different mechanical and civil structures. Some of them are strain based methods in which abruptly increased strain signifies the presence of damage in the structure. This article focuses on crack monitoring of a fixedfixed beam using fiber optic sensors which can measure strain locally or globally. The two types of fiber optic sensors used in this research are fiber Bragg grating (FBG) and fiber optic polarimetric sensors (FOPS). FBG and FOPS are used for local strain monitoring (at one point only) and global strain monitoring (in the entire specimen) respectively. At the centre of the specimen, a piezoelectric wafer active sensor (PWAS) is also attached. PWAS is used to obtain electromechanical admittance (EMA) signatures. Further, these EMA signatures are analysed to access the damage state in the beam. These multiple smart materials together provide improved information on damages in the specimen which is very valuable for the structural health monitoring (SHM) of the specimen.